A Review of the Recent Advances in Cyclic Butylene Terephthalate Technology and its Composites. Issue 3 (4th May 2017) - Abt, Tobias; Sánchez-Soto, Miguel
ABSTRACT: Cyclic butylene terephthalate (CBT®) oligomers are a relatively new class of material and are capable of polymerizing in an entropically driven ring-opening polymerization into high-molecular-weight polymerized CBT (pCBT) in very short times, i.e., within minutes. The most important feature of CBT is its very low, water-like melt viscosity prior to polymerization which gives rise to an excellent impregnation of fibrous reinforcements in contrast to conventional, high viscous thermoplastic resins. This opens up new possibilities in the thermoplastic composite production since thermoplastic-based composites show some advantages over thermoset-based ones. Specifically, they have a higher toughness and impact strength and they can be welded, postformed, and recycled due to their thermoplastic nature. CBT has the potential to substitute thermoset matrices in fiber-reinforced composites and may solve some of the today´s recycling issues associated with thermoset-based composites. Moreover, the low melt viscosity of CBT enhances the dispersion of nano- or conductive particles and can yield superior nano- and conductive composites. This article reviews the recent advances in processing–structure–property relationship, physical and chemical modification of pCBT, as well as the preparation of fiber-reinforced pCBT composites, pCBT nanocomposites, and conductive pCBT composites.